The texture-taste connection: Multimodal sensory neurons in fly larvae. - Katrin Vogt (PLoS Biology)
Eating is a multisensory experience: food's smell, look, and texture are as important as taste. A new study in PLOS Biology shows that fly larvae respond to food texture and integrate information from different modalities within a single gustatory neuron.